Uji Resistensi Larva Nyamuk Aedes Aegypty Terhadap Temepos (Abate) Pada Daerah Endemis DBD Di Kota Kendari Sulawesi Tenggara : Assessment of Aedes aegypti Larval Resistance to Temephos (Abate) in Dengue-Endemic Regions of Kendari, Southeast Sulawesi - Nurqomaria, Nurqomaria; Oktaviani, Elis; Helmia, Najma; Sriswanti, Sriswanti; Kurniawan Putra, Agus (Aspirator, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health issue in Kendari City, Southeast Sulawesi. Larvicidal insecticides such as temephos (Abate) are commonly used for vector control; however, repeated use may lead to resistance in Aedes aegypti populations.This study aimed to assess the resistance level of Aedes aegypti larvae to temephos in dengue-endemic areas of Kendari City.Laboratory tests were conducted at the Entomology and Parasitology Laboratory of Mandala Waluya University. Larvae were collected from three endemic sub-districts: Baruga, Kadia, and Poasia. Resistance was tested using temephos at concentrations of 0.005 mg/L, 0.01 mg/L, 0.02 mg/L, and 0.03 mg/L. Each treatment was replicated three times with 25 larvae per replicate. Mortality was recorded after 24 hours of exposure. All tested populations demonstrated resistance, with larval mortality rates remaining below 80% across all concentrations. In Baruga, the highest mortality (60%) occurred at 0.03 mg/L with an LC₅₀ of 0.023 mg/L. In Kadia, the highest mortality was 42.66%. In Poasia, 49.33% mortality was observed at 0.03 mg/L with an LC₅₀ of 0.043 mg/L. No mortality was observed in the control group, thus Abbott's correction was not applied. Aedes aegypti larvae from dengue-endemic regions in Kendari City exhibited resistance to temephos at all tested concentrations. These findings highlight the need for reevaluation of larvicide use and implementation of integrated vector control strategies.